Definition of capacity of a shunting diesel locomotive in view of a place of his operation - Сиротенко, Юрій Валентинович (Eastern-European Journal of Enterprise Technologies, 2014)
The method for determining the capacity of shunting diesel locomotives in view of their operation features, based on using the regression analysis is given in the paper. Herewith, the main objective of the research was to identify new relationships between the factors, which practically are not considered today by current standard indicators. Using modern technical solutions allowed to create a special electronic system (mode-meter), which allowed to quantify the useful operation time of shunting locomotive per a working shift, its loading level by various shunting operations, as well as compare them with the locomotive fuel economy. Based on the regression analysis, simulation of these parameters, which allowed to determine the necessary capacity level of its propulsion system during operation at a specific worksite was conducted. The significance and importance of coefficients of the obtained regression equation was defined on PC using special software. At that, the obtained function was tested for extremum, and the optimal values of its components were found. Based on the simulation results, universal nomograms for practical definition of the required power of shunting diesel locomotives to perform simple station and hump-export works depending on the volume, capacity utilization factor, time of locomotive useful operation per shift (for station shunting) or shunting stock mass (for hump-export works), as well as fuel consumption per shift were developed.